Selection of Potential Probiotic Yeasts from Dry-Cured Xuanwei Ham and Identification of Yeast-Derived Antioxidant Peptides - Jiaming Cai; Lujuan Xing; Wangang Zhang; Lijuan Fu; Jian Zhang (Antioxidants, 2022)
The aim of this study was to select potential probiotic yeasts from dry-cured Xuanwei ham and investigate yeast-derived antioxidant peptides. The results showed that two strains (XHY69 and XHY79) were selected as potential probiotic yeasts and identified as Yamadazyma triangularis. The two yeasts showed tolerance under pH 2.5 and 1% bile salt, in addition to protease activity, auto-aggregation, antibacterial, and antioxidant activities. The peptide fraction (MW < 3 kDa) isolated from XHY69 fermentation broth, named XHY69AP, showed higher radical scavenging activities than glutathione at a concentration of 4.5 mg/mL (p < 0.05). The fraction (AP-D10) was purified from XHY69AP by gel filtration chromatography and reversed-phase high performance liquid chromatography, and then further identified by a UHPLC-LTQ-Orbitrap mass spectrometer. The molecular weight of all 55 purified sequences was distributed between 0.370 and 0.735 kDa. Among these seven novel peptides, Tyr-Pro-Leu-Pro (YPLP), Ala-Gly-Pro-Leu (AGPL), Gly-Pro-Phe-Pro (GPFP), and Ala-Pro-Gly-Gly-Phe (APGGF) were identified. All sequences were abundant in hydrophobic amino acids, especially proline residue. Among these novel peptides, YPLP possessed the highest ABTS scavenging rate (75.48%). The present work selects two new probiotic potential yeasts from dry-cured Xuanwei ham that are effective to yield novel antioxidant peptides.